Judicial precedent regarding the exercise of discretion in the application of financial legal provisions - Barikova, Anna (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
Applying judicial precedent as a source of law will contribute to the implementation of the principle of legal certainty and will, in fact, testify to the already existing practice.The purpose of the article is to reveal the aim and functions of judicial precedent regarding the exercise of discretion in the application of financial legal provisions.It has been proven that a prospective legal precedent within the framework of legal judicial doctrine is a source of law in the application of financial legal provisions. This is a convincing precedent” during judicial activism, when legal positions in the decisions of the highest judicial authorities (at the national level, as well as supranational) acquire the force of a legal norm of “living law”, outline the limits of the exercise of discretion, regarding the authority of such rule makers, and as well as their right to annul court decisions of judicial authorities of previous instances. At the same time, all judges have the right to issue decisions contrary to such legal conclusions, with appropriate reasoning. The author has adduced arguments why the court decision does not simply quote the provisions of the current legislation, but creates new “living” norms. It is about dynamic interpretation, as a result of which documents become “alive” thanks to the activity of interpreting judges. In case of uncertainty, ambiguity or conflict of such norms, the judge is to go beyond the text to the fundamental guidelines. The formation of judicial precedent is influenced by changing manifestations of existence in its historiography and development, considering legal, moral, religious, civilizational, national, globalized and other factors. It has been established that during the interpretation of the meaning of the text, the rules of its application to the facts of the case are formed. The consequence of such an interpretation is a new understanding of the law, expressed in the legal position in the motivational part of the court decision, thanks to which the case is resolved. The described process is discursive, dynamic, takes into account the specific circumstances of the case and historical, socio-cultural, economic and other manifestations of reality.